Preserving Local Sustainability As A Pillar Of The Beach Tourism Continuity in Tanjung Batu Village Of Saoka Sub-District - Zulfajri Rumkel; Jusmin Jusmin (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
This research aims to formulate a strategy to optimize the management of Tanjung Batu Beach tourism to increase tourist visits and ensure sustainable tourism in Saoka Village, Sorong City. The method used is qualitative, with data collection techniques through observation, interviews, and documentation. The results showed that Tanjung Batu Beach has great natural potential but still faces various obstacles, including infrastructure limitations, a lack of supporting facilities, limited digital promotion, and minimal local community participation. The management strategy focuses on preserving the beach's authenticity and naturalness, improving basic facilities such as bathrooms and sales areas for local communities, and maintaining cleanliness and environmental sustainability. Tourism sustainability is pursued by minimizing modern development that could alter the beach's natural character and by involving the community in destination management and promotion. Strategies to increase tourist visits to Tanjung Batu Beach, Saoka Village. Through tourism management and development strategies that focus on preserving the beach's authenticity and naturalness. The sustainability approach focuses on maintaining the beach's authenticity and preservation independently, without the involvement of outside parties. However, the manager of Tanjung Batu Beach currently faces annual losses due to theft from the water reservoirs, so they must continue to buy replacements. In addressing these challenges, this study also emphasizes the importance of adopting a more integrated and participatory approach to managing tourism at Tanjung Batu Beach.